The Role of Atypical Chemokine Receptor D6 (ACKR2) in Physiological and Pathological Conditions; Friend, Foe, or Both? - Gowhari Shabgah, Arezoo; Jadidi-Niaragh, Farhad; Mohammadi, Hamed; Ebrahimzadeh, Farnoosh; Oveisee, Maziar; Jahanara, Abbas; Gholizadeh Navashenaq, Jamshid (Frontiers in Immunology, 2022)
Chemokines exert crucial roles in inducing immune responses through ligation to their canonical receptors. Besides these receptors, there are other atypical chemokine receptors (ACKR1-4) that can bind to a wide range of chemokines and carry out various functions in the body. ACKR2, due to its ability to bind various CC chemokines, has attracted much attention during the past few years. ACKR2 has been shown to be expressed in different cells, including trophoblasts, myeloid cells, and especially lymphoid endothelial cells. In terms of molecular functions, ACKR2 scavenges various inflammatory chemokines and affects inflammatory microenvironments. In the period of pregnancy and fetal development, ACKR2 plays a pivotal role in maintaining the fetus from inflammatory reactions and inhibiting subsequent abortion. In adults, ACKR2 due to scavenging inflammatory chemokines is considered a resolving agent in the body, which leads to the alleviation of inflammation in various conditions, including cardiovascular diseases, autoimmune diseases, neurological disorders, infections, etc. In cancer, ACKR2 exerts conflicting roles, either tumor-promoting or tumor-suppressing. On the one hand, ACKR2 inhibits the recruitment of tumor-promoting cells and suppresses tumor-promoting inflammation to blockade inflammatory responses that are favorable for tumor growth. In contrast, scavenging chemokines in the tumor microenvironment might lead to disruption in NK cell recruitment to the tumor microenvironment. Other than its involvement in diseases, analyzing the expression of ACKR2 in body fluids and tissues can be used as a biomarker for diseases. In conclusion, this review study has tried to shed more light on the various effects of ACKR2 on different inflammatory conditions.